2014
DOI: 10.1097/jom.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Inducing a Health-Promoting Change Process Within an Organization

Abstract: The change process initiated by the large-scale intervention contributed to a social climate in the workplace that promoted health and ownership toward health. The study confirms the relevance of collective change processes for health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…This was rated as weak which at best leads to an overall moderate study quality. Four studies [20,21,22,23] had a weak overall methodological quality which was mainly due to selection bias, no blinding of participants or outcome assessors, and a low follow-up rate. One of these four studies was very weak, scoring low on five out of six criteria [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was rated as weak which at best leads to an overall moderate study quality. Four studies [20,21,22,23] had a weak overall methodological quality which was mainly due to selection bias, no blinding of participants or outcome assessors, and a low follow-up rate. One of these four studies was very weak, scoring low on five out of six criteria [23].…”
Section: Resultsmentioning
confidence: 99%
“…The study of Van Scheppingen et al [22] evaluated a large-scale intervention to induce a health- promoting organizational change process in a population of employees in a dairy company. The intervention consisted of three main components: (1) dialogue sessions aimed at reflecting on the value of health and vitality at work among employees and at putting this on the personal agenda of employees and the organization, (2) vitality-promoting activities at the department level, such as lunch walks or workshops on healthy work postures, and (3) physical activities in which employees could participate individually, such as running races and team sports activities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, specific supervisor openness towards employees has shown to be connected with employee safety (Tucker and Turner 2015 ). And a study by van Scheppingen et al found that implementation of increased dialogue and communication between employees and between employees and managers increased the openness about health at these levels in the organization (van Scheppingen et al 2014 ). Still how openness at the different levels of the organization impacts the management of pain in the organization remains to be studied.…”
Section: Discussionmentioning
confidence: 99%